The Democratic Implications of Civil Society in China - He, B. author. aut Link
XI, 212 p.
Keywords: This book discusses the roles of civil society in the initiation stage of democratization in China. It argues that there is a semi-civil society in China and that this quasi-civil society that plays dual roles in the initial stage of democratisation in China. It makes a contribution to existing theories on democratic functions of civil society by applying, testing, revising and developing these theories in the context of Chinese democratization.